Correlation of Mothers’ Knowledge and Employment Status with Exclusive Breastfeeding in Sidotopo - Riza Ramli (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2020)
Background: Low level of knowledge about exclusive breastfeeding and mother's employment status become factors causing flawed exclusive breastfeeding in Indonesia. The high number of working mothers makes babies unable to be exclusively breastfed. Objective: This study determined the relationship of knowledge and mother's employment status with exclusive breastfeeding in Sidotopo. Method: This study was a descriptive analytical study with a cross-sectional design. The sampling technique used purposive sampling with a total sample of 57 respondents. The primary data were collected through questionnaires and then analyzed by using chi-square test. Results: There were 52 mothers (91%) who did not exclusively breastfeed. Most of them (94.4%) had insufficient knowledge and did not exclusively breastfeed. The number of mothers who had good knowledge and exclusively breastfed was only 3 mothers (14.3%). Most mothers (73.7%) who did not work did not exclusively breastfed their babies (90.5%). Among 15 working mothers (26.3%), only 1 mother (6.7%) exclusively breastfed. Based on the bivariate analysis test, there was no relationship of mother's knowledge with exclusive breastfeeding (P value = 0.346 > 0.05). There was no relationship of mother's employment status with exclusive breastfeeding (P value= 0.604 <0.05). Conclusion: Environment and habits of providing complementary food to babies aged less than 6 months are difficult to avoid it, and thus babies cannot gain the benefits of exclusive breastfeeding.